Analisa Pengaruh Komunikasi Marketing dan Kepercayaan terhadap Loyalitas Melalui Kepuasan Nasabah pada PT BPR Eka Dana Mandiri (Bank Edaman) Malang - Kiswinarso, Alberken Sih; R, Ike Kusdyah; Handoko, Yunus (J-MAS (Jurnal Manajemen dan Sains), 2024)
PT. Eka Dana Mandiri(Bank Edaman) Malang as a banking institution provides financial services for consumers in the Greater Malang area and its surroundings and participates in advancing the economy in the Greater Malang area and its surroundings PT. Eka Dana Mandiri(Bank Edaman) in the midst of competition between financial institutions is required to be able to provide the best service in terms of marketing communications and trust so that it has an impact on the sustainability of the company's business. The end of the transition from the Covid-19 pandemic to the New Normal for PT customers. BPR Eka Dana Mandiri(Bank Edaman) Malang experienced a decline in the number of customers. This type of research is a quantitative approach. The population in this research are customers who make loans to PT. BPR Eka Dana Mandiri(Bank Edaman) Malang. A total of 46 customers at PT. BPR Eka Dana Mandiri(Bank Edaman) Malang as a respondent came and met with researchers to fill out the questionnaire. This type of research is a quantitative approach. The population in this research is customers at PT. BPR Eka Dana Mandiri(Bank Edaman) Malang. 46 Customers at PT. BPR Eka Dana Mandiri(Bank Edaman) Malang as a respondent came and met with researchers to fill out the questionnaire. The results of this research show, among other things: 1) Marketing Communication has a direct and significant effect on Customer Loyalty; 2) Trust has a direct and significant effect on Customer Loyalty; 3) Marketing Communication has a direct and significant effect on Customer Satisfaction; 4) Trust has a direct and significant effect on Customer Satisfaction; 5) Satisfaction has a direct and significant effect on Customer Loyalty; 6) Marketing Communication has an indirect effect on Loyalty through significant Customer Satisfaction; and 7) Trust has an indirect effect on Loyalty through significant Customer Satisfaction.